Evaluation of coriander seed powder supplementation on body composition, growth performance, hematology, and serum biochemical indices in common carp (Cyprinus carpio) fingerlings: Effects of coriander lementation on common carp - Ahmed Qader, Zena; Sofy Omar, Samad (Cellular and Molecular Biology, 2024)
This study aimed to investigate the role of coriander seed powder (Coriandrum sativum) on growth indices, feed utilization, body composition, and haemato-biochemical parameters in common carp (Cyprinus carpio) fingerlings over 84 days. One hundred and forty-four common carp (25.24±0.05 g) were assigned into four groups fed with different diets, namely 0 (basal diet), 1%, 2%, and 4% of coriander seed powder (CSP). In the current study, C. carpio fed with dietary CSP revealed significant improvement in weight gain, final weight, specific growth rate, total feed intake, feed conversion efficiency, feed conversion ratio, protein intake, and protein efficiency ratio, in comparison to control fish fed after 84 days (P>0.05). It was also found that fish fed with 1%CSP-supplemented dietary had the best growth performance and feed utilization. The crude protein of fish fed with CSP dietary treatments increased, and significant differences were only found in the fish fed with 1%CSP diet, in comparison to the control group. The CSP supplementation groups showed significant increases in hemoglobin, hematocrit, albumin, total protein, and globulin compared to the control group. Nevertheless, differential white blood cells, mean corpuscular hemoglobin concentration, cholesterols, and triglycerides were significantly reduced in the CSP dietary group in comparison to the control group. It was also found that CSP dietary treatment significantly increased lipase and amylase in comparison to the control group (P>0.05). However, the highest lipase and amylase levels were obtained at 1%CSP and 2%CSP dietary treatment groups, compared to the control basal diet. Based on the results, CSP supplementation could improve the overall health status and growth performance of common carp fingerlings.